An introduction to mathematical proofs - Loehr, Nicholas A. ([Boca Raton, Florida] : [CRC Press], 2020)
'This book contains an introduction to mathematical proofs, including fundamental material on logic, proof methods, set theory, number theory, relations, functions, cardinality, and the real number system. The book is divided into approximately fifty brief lectures. Each lecture corresponds rather closely to a single class meeting'--
Logic -- Proofs -- Sets -- Integers -- Relations and functions -- Equivalence relations and partial orders -- Cardinality -- Real numbers (optional).
Includes bibliographical references and index.
Keywords: Proof theory -- Textbooks